Mouse Lung Fibroblast Resistance to Fas-Mediated Apoptosis Is Dependent on the Baculoviral Inhibitor of Apoptosis Protein 4 and the Cellular FLICE-Inhibitory Protein - Predescu, Sanda A.; Zhang, Jian; Bardita, Cristina; Patel, Monal; Godbole, Varun; Predescu, Dan N. (Frontiers in Physiology, 2017)
A characteristic feature of idiopathic pulmonary fibrosis (IPF) is accumulation of apoptotic resistant fibroblasts/myofibroblasts in the fibroblastic foci. As caveolin (Cav)-null mice develop pulmonary fibrosis (PF), we hypothesized that the participating fibroblasts display an apoptosis-resistant phenotype. To test this hypothesis and identify the molecular mechanisms involved we isolated lung fibroblasts from Cav-null mice and examined the expression of several inhibitors of apoptosis (IAPs), of c-FLIP, of Bcl-2 proteins and of the death receptor CD95/Fas. We found significant increase in XIAP and c-FLIP constitutive protein expression with no alteration of Bcl-2 and lower levels of CD95/Fas. The isolated fibroblasts were then treated with the CD95/Fas ligand (FasL) to induce apoptosis. While the morphological and biochemical alterations induced by FasL were similar in wild-type (wt) and Cav-null mouse lung fibroblasts, the time course and the extent of the alterations were greater in the Cav-null fibroblasts. Several salient features of Cav-null fibroblasts response such as loss of membrane potential, fragmentation of the mitochondrial continuum concurrent with caspase-8 activation and subsequent Bid cleavage, prior to caspase-3 activation were detected. Furthermore, M30 antigen formation, phosphatidylserine expression and DNA fragmentation were caspase-3 dependent. siRNA-mediated silencing of XIAP and c-FLIP, individually or combined, enhanced the sensitivity of lung fibroblasts to FasL-induced apoptosis. Pharmacological inhibition of Bcl-2 had no effect. Together our findings support a mechanism in which CD95/Fas engagement activates caspase-8, inducing mitochondrial apoptosis through Bid cleavage. XIAP and c-FLIP fine tune this process in a cell-type specific manner.